2016
DOI: 10.1089/jop.2016.0069
|View full text |Cite|
|
Sign up to set email alerts
|

Prostanoid Receptor Antagonist Effects on Intraocular Pressure, Supported by Ocular Biodisposition Experiments

Abstract: These antagonist studies provided no evidence for individual endogenous prostanoids exerting a meaningful role in regulating IOP. They do reaffirm the critical importance of studying ocular bioavailability for confirming negative data. Large differences among the antagonists in anterior segment and even ocular surface tissue biodisposition were observed in rabbits. It appears from these monkey studies, supported by rabbit ocular bioavailability data, that an absence of drug effect in the eye cannot be adequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The pharmacokinetic methods were previously and extensively described. 31 The pharmacokinetic studies presented herein were performed at Medicilon Preclinical Research (Shanghai) LLC (Shanghai, China). Male New Zealand white rabbits, weighing 1.79 to 2.95 kg, were used in the study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The pharmacokinetic methods were previously and extensively described. 31 The pharmacokinetic studies presented herein were performed at Medicilon Preclinical Research (Shanghai) LLC (Shanghai, China). Male New Zealand white rabbits, weighing 1.79 to 2.95 kg, were used in the study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Membranes were prepared from 1321 NI astrocytoma cells (Sigma‐Aldrich, Gillingham, Dorset, UK)) stably expressing human recombinant DP 1 receptors (Woodward et al, , Wang et al, ). For assays, membranes (protein 15 μg per well) expressing the human DP 1 receptor were incubated in Millipore Multiscreen HTS ‐HV (0.45 μm) plates containing assay buffer (50 mM Tris, 5 mM MgCl 2 , 10 μg·mL −1 saponin and 10 mM indomethacin), [ 3 H] PGD 2 3.2 nM and the test compounds (0.1 to 10 000 nM) at pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…The periorbital delivery method may mitigate adverse effects and present a pharmacologic advantage. It has been shown that bimatoprost tends to accumulate in the eyelids and palpebral conjunctiva 54,55 . As the palpebral conjunctiva overlies the limbus and sclera, and scleral penetration of prostanoid drugs is comparatively higher than via the cornea, application of very potent drugs like EP2 agonists via the periocular tissue may provide a slow‐release drug depot, presuming that this tissue will more slowly hydrolyze the ester 53 .…”
Section: Prostaglandin Devicesmentioning
confidence: 99%